PRAGMATIC INTERPRETATION OF THE CONCEPTS OF PATIENCE AND ENDURANCE (TAMADDUN NURI JURNALI, 2024)
This article explores the concepts of patience and endurance through a pragmatic lens, examining their implications in everyday life, psychological resilience, and social interactions. By drawing upon various philosophical, psychological, and sociolinguistic perspectives, the paper aims to elucidate the nuanced meanings of these concepts and their relevance in contemporary society. The study highlights how patience and endurance are not merely passive traits but active skills that can be cultivated and applied in various contexts, thus contributing to personal growth and social harmony.